Juegos tradicionales para fomentar el trabajo en equipo a los estudiantes de 10 años de la Unidad Educativa Siglo XXI - Fajardo Cedeño, Kening Hernany (2025)
This research on traditional games to promote teamwork in 10th grade students of the Siglo XXI Educational Unit. Traditional games are considered as playful expressions that are part of the customs and traditions of a people. This implies that their value in the construction of morality is not insignificant; contrary to what would be simply recreational and higher than mere pleasure for the senses. The game is a motivating activity that favors the practice of physical exercise, it is a means of connection and enjoyment, at the same time it is enhanced in four areas of development: motor, affective, social and intellectual. These recreational phenomena, in addition to consolidating traditional and cultural identity, can promote social trust and boost the teaching process within educational contexts; since they have an invaluable pedagogical value. Methodology: a mixed approach, with qualitative and quantitative methods, descriptive research type, an exploratory design and field research. It will allow to observe and evaluate the importance of traditional games to promote teamwork in 10-year-old students of the Siglo XXI Educational Unit. The data collection techniques will be an interview and an observation sheet. Results: It was determined that 69.2% of 10-year-old students of the Siglo XXI Educational Unit never participate in team school activities. While 23.1% rarely participate in team school activities. In addition, there are many students who are isolated when doing teamwork. Therefore, traditional games are an appropriate strategy to promote teamwork.